2006
DOI: 10.1063/1.2234560
|View full text |Cite
|
Sign up to set email alerts
|

Near-field thermophotovoltaic energy conversion

Abstract: We report a quantitative model of a near-field thermophotovoltaic (TPV) device consisting in a thermal source located in the near field of a TPV cell. The enhanced radiative transfer at short distance leads to an increase of the photogeneration current. We analyze quantitatively other potential near-field effects, in particular, on the dark current. We also study the influence of the modification of the spectrum of the sources in the near field, comparing the case of a tungsten source with the case of a quasim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
291
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(293 citation statements)
references
References 32 publications
2
291
0
Order By: Relevance
“…It was previously suggested that in NF, surface excitations can enhance the performance of TPV devices beyond the blackbody limit such that larger efficiencies are reached at lower operation temperatures. The almost monochromatic behavior of NF RHT could yield higher energy conversion efficiencies when properly matched to the bandgap of the PV diodes [17][18][19][20]. For example, the frequency of plasmons depends on the carrier density, and can therefore be changed by doping, in materials such as silicon.…”
Section: *Corresponding Authors; Petervanzwol@gmailcom Joelchevriementioning
confidence: 99%
See 1 more Smart Citation
“…It was previously suggested that in NF, surface excitations can enhance the performance of TPV devices beyond the blackbody limit such that larger efficiencies are reached at lower operation temperatures. The almost monochromatic behavior of NF RHT could yield higher energy conversion efficiencies when properly matched to the bandgap of the PV diodes [17][18][19][20]. For example, the frequency of plasmons depends on the carrier density, and can therefore be changed by doping, in materials such as silicon.…”
Section: *Corresponding Authors; Petervanzwol@gmailcom Joelchevriementioning
confidence: 99%
“…New opportunities in NF have recently emerged for thermo photo voltaics (TPV) [17][18][19][20]. It was previously suggested that in NF, surface excitations can enhance the performance of TPV devices beyond the blackbody limit such that larger efficiencies are reached at lower operation temperatures.…”
Section: *Corresponding Authors; Petervanzwol@gmailcom Joelchevriementioning
confidence: 99%
“…For example, near-field HT is an important mechanism for practical applications in energy storage and conversion, thermal management and thermal circuits, nearfield imaging and nanomanufacturing [47][48][49][50][51]. Manybody aspects of HT are especially important for implementation of devices controlling the heat flux, so-called thermal transistors [34,51].…”
Section: Introductionmentioning
confidence: 99%
“…Near-field radiation has attracted much attention in the fields of energy harvesting [1,2] and heat management [3][4][5] since it can exceed the far-field blackbody limit through coupling of evanescent waves [6,7]. In particular, the near-field enhancement could be orders of magnitude with the excitation of surface plasmon/phonon polaritons (SPP/SPhP) across the nanometer vacuum gaps [8][9][10][11]; however, it usually requires identical or similar materials for the emitter and receiver to achieve the best coupling effect and thereby maximum heat flux enhancement.…”
Section: Introductionmentioning
confidence: 99%